IMPLEMENTASI METODE ACCESS CONTROL LIST PADA MIKROTIK DALAM MENGAMANKAN JARINGAN INTERNET DI KANTOR LURAH AIR SELEMBA - Rahmat Sulaiman; Rab Sahf Al Fathul; Agustina Mardeka Raya (Lembaga Pengembangan Kinerja Dosen, 2024)
To meet the minnimum requirements of people who want to get information quickly and easily, the need for internet access is very high. Thus, we must continue to look for and strive for quality. There is a delay in communication and there is no filtering for devices connected to Office of Salemba’s internet. This is because there is no way to regulate the access rights for each device on the network, therefore it is necessary to implement the Access Control List (ACL) method on computer networks with the aim of making staff or employees more stable when working. In getting internet access, the development used is NDLC consisting of Analysis, Design, Prototyping Simulation, Implementation, Monitoring and Management. Data collection methods are literature study, observation and interviews. The routerboard that has been used is RB941-2nd. The results obtained from this research are that this method is very helpful in limiting the number of clients who get the internet and filtering unauthorized packets.